Screen Time and Arrested Social Development Across All Ages (East West Medical College Journal, 2025)
In recent years, the exponential increase in screen time across all demographics has sparked significant concerns among psychologists, educators, and parents alike. The digital world has opened unprecedented opportunities for connectivity, learning, and convenience, yet it has also introduced new challenges that touch every stage of human development. One major issue is the impact of screen time on social development, which is critical not only for children and teenagers but also for adults who are experiencing arrested social development in various ways. This editorial explores the potential risks of excessive screen time and advocates for mindful usage across all age groups.EWMCJ Vol. 13, No. 1, January 2025: 1-3